e-Little Hajj: The Development of Augmented Reality Mobile Learning Apps to Enhance Learning Experience in Performing Hajj for Preschool - Mohd Hatta Mohamed Ali @ Md Hani; Hanie Umi Sofea Mohamad Nizam; Aisyah Syarah Abdul Rahman; Hazlyana Ab Karim (Multidisciplinary Applied Research and Innovation, 2023)
Hajj is an annual pilgrimage to Mecca taken by capable Muslims who have to complete it at least once in their lives. This is the fifth of the five pillars of Islam and brings full rewards, benefits, and forgiveness from Allah SWT. The COVID-19 pandemic, which is affecting Malaysia as well as the rest of the world, presents a challenge for learning hajj at this time, just as it does for other subjects. As a result, to maintain the continuity of education, all learning activities are now focused on teaching and learning from home (PdPR). With preschools now offering Hajj learning curricula to their students to foster understanding and interest in performing Hajj, learning about Hajj is no longer restricted to adults. Practical Hajj is done by preschool students through the subjects of Hajj and Umrah. In this critical situation, students find it difficult to learn practical Hajj because the learning is done online. As a result, we will create a mobile learning application that contains the AR code by employing Zappar. Each AR code has an animation video on how to perform the Hajj. Therefore, this project can help students perform a better Hajj. Thus, the children can learn even though they are at home. They can also understand better the concept, reasons, and procedures for performing hajj. Students can learn Hajj at any time as there is a guide in the e-Little Hajj mobile learning application. For example, students simply scan the AR code to see the animation video on how to perform Hajj.